Ketersediaan Tempat Bermain/Berolahraga Di Sekolah Dasar Negeri Se-Kecamatan Demak Kabupaten Demak (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the availability and standardization of playgrounds/sports in public elementary schools throughout the Demak District, Demak Regency. This study uses a mixed research method (mix-method). The sample collection technique that will be used is Proportional Random Sampling. The sample to be studied in this study is a place to play/exercise in State Elementary Schools throughout the Demak District, Demak Regency, amounting to 6 State Elementary Schools. Collecting data using observation, interviews, and documentation. The results of the research from the availability and standardization of playgrounds/sports that the availability in elementary schools throughout the Demak District, Demak Regency is good and standardization still has shortcomings where the results obtained in the field are not fully above the standard but there are some that are still below the standard. The conclusion from the research is the availability of public elementary schools in Demak District, Demak Regency in good condition and used properly. And the standardization of public elementary schools throughout the Demak District, Demak Regency is stated to still have shortcomings where the results obtained in the field are not fully above the standard, but there are some that are still below the standard.